(untitled) (European Journal of Language and Literature, 2017)
There are two major interrelated reasons behind examining the topic of this paper. In fact, even after many years of their learning English as a foreign language, a large number of secondary school students’ level of proficiency in the language is so low that they cannot use it communicatively, and cannot major in it at university, either. Accounting for their underachievement, a large percentage of such students claim that many teachers still play traditional roles in the teaching-learning process, which has contributed to the problem. The main purpose of this paper, therefore, is to explore the extent to which such a claim is justifiable. In this frame of reference, a questionnaire was administered to a certain number of students on the extent to which the teacher is responsible for the issue, as well as what they personally think the key characteristics of a successful EFL teacher are. Along with this, the paper will equally look at other qualities that ought to be available in EFL teachers with the overall aim of helping them to do their job successfully, and hence attain the expected learning results.